Characterization of Factors Involved in Localized Translation Near Mitochondria by Ribosome-Proximity Labeling - Vardi-Oknin, Dikla; Arava, Yoav (Frontiers in Cell and Developmental Biology, 2019)
Mitochondria exert their many functions through a repertoire of hundreds of proteins. The vast majority of these proteins are encoded in the nuclear genome, translated in the cytosol and imported into the mitochondria. Current models, derived mainly from work in yeast, suggest that the translation of many of these proteins can occur in close vicinity to the mitochondria outer membrane by localized ribosomes. Here we applied ribosome-proximity biotin labeling to address this possibility. A clear biotinylation of ribosomes by mitochondrial Tom20-BirA fusion protein was observed in a human cell line. Isolation of these ribosomes revealed their preferred association with mRNAs encoding mitochondrial proteins. Furthermore, knock down of the mitochondrial protein receptor Tom70 resulted in a decrease in ribosomes translating mRNAs encoding proteins predicted to be recognized by Tom70. Intriguingly, levels of ribosomes translating mRNAs encoding targets of Tom20 were increased. We also knocked down the RNA binding protein CLUH that is implicated in regulation of mRNA encoding mitochondrial proteins, and found an increase in association of CLUH targets with mitochondria-proximal ribosomes. This is consistent with a role for CLUH in maintaining mRNAs encoding mitochondrial proteins in the cytosol. Overall, these data shed light on factors that contribute to association of translating ribosomes with human mitochondria and may suggest a co-translational mode of protein import into this organelle.